Kajian Viktimologi Orang Dengan Gangguan Jiwa Sebagai Korban Penganiayaan - Mailoa, Mikhael Patric Jansen; Latupeirissa, Julianus Edwin; Taufik, Iqbal (PATTIMURA Law Study Review, 2024)
ABSTRACT: Persecution is an act against the law, so there are many actions that can be carried out by irresponsible people, where an act of covering up what happened can be in the form of torturing, thinking, etc. An act of drawing can occur intentionally or unintentionally so it can also result in the death of a human victim. For example, the transmission case that occurred in Masohi was a victim of a person with a mental disorder, where the suspect named Ancamali carried out the transmission to a person with a mental disorder and also burned the person with a mental disorder, resulting in the victim dying, so Ancamali received a prison sentence of 4 years and 6 months. The problem that the author can discuss is how to study the victimology of people with mental disorders (ODGJ) who are victims of abuse and how to deal with people with mental disorders who become human victims. This writing uses the Normative Juridical research type, with a statutory regulation approach, a conceptual approach and a case approach. The results of the research show that actions carried out by irresponsible people are mandatory and must be held accountable in accordance with applicable regulations, in article 338 of the criminal code which states "whoever deliberately takes the life of another person is threatened because murder with a maximum prison sentence of fifteen years.” as well as efforts to handle people with mental disorders who become human victims, can be done through preventive and repressive efforts.